2018
DOI: 10.3390/ma11081382
|View full text |Cite
|
Sign up to set email alerts
|

Surface Quality Enhancement of Fused Deposition Modeling (FDM) Printed Samples Based on the Selection of Critical Printing Parameters

Abstract: The present paper shows an experimental study on additive manufacturing for obtaining samples of polylactic acid (PLA). The process used for manufacturing these samples was fused deposition modeling (FDM). Little attention to the surface quality obtained in additive manufacturing processes has been paid by the research community. So, this paper aims at filling this gap. The goal of the study is the recognition of critical factors in FDM processes for reducing surface roughness. Two different types of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
89
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 32 publications
(39 reference statements)
9
89
1
2
Order By: Relevance
“…The opposite is observed at low temperatures, thin layers, and slow speeds, because the filament creates blobs due to its high viscosity, the slow speed does not stretch the filament, and thin layers cool rapidly. The investigations of Peng et al [27], Pérez et al [28],Yang et al [32], and Huang et al [33] confirm the results of this study that layer thickness greatly influences the surface quality. Raju et al [29] also ascribe this result to the staircase effect.…”
Section: Surface Roughnesssupporting
confidence: 82%
See 1 more Smart Citation
“…The opposite is observed at low temperatures, thin layers, and slow speeds, because the filament creates blobs due to its high viscosity, the slow speed does not stretch the filament, and thin layers cool rapidly. The investigations of Peng et al [27], Pérez et al [28],Yang et al [32], and Huang et al [33] confirm the results of this study that layer thickness greatly influences the surface quality. Raju et al [29] also ascribe this result to the staircase effect.…”
Section: Surface Roughnesssupporting
confidence: 82%
“…Therefore, layer thickness is a conflicting factor, but the energy consumption can be reduced by increasing printing speed while maintaining a good surface quality. Pérez et al [28] inspected the effect of layer thickness, printing speed, temperature, and wall thickness (contour thickness) on the surface roughness. Using analysis of variance, layer thickness and wall thickness were identified as critical factors, while printing speed and temperature seemed to have less influence.…”
Section: Introductionmentioning
confidence: 99%
“…They drew a conclusion that a lack of pigmentation and a low extrusion temperature were preferable for better surface quality. Unlike most of the previously mentioned research, Pérez et al [63] used a cylindrical-shaped specimen instead of a cuboid-shaped specimen. In their study, layer thickness, print speed, extrusion temperature, and shell thickness were the analyzed parameters.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Raju et al optimized the FDM process parameters by using the hybrid particle swarm and bacterial foraging optimization (PSO‐BFO) evolutionary algorithm. Pérez et al experimentally studied the effect of printing parameters on the surface roughness of FDM parts. They found that layer height and wall thickness were the most important factors for controlling surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…They found that layer height and wall thickness were the most important factors for controlling surface roughness. The main advantages of this technology include: wide variety of materials, low maintenance costs, cheap printing equipment, less pollution, and facile manipulation …”
Section: Introductionmentioning
confidence: 99%